2023
DOI: 10.1093/hmg/ddad012
|View full text |Cite
|
Sign up to set email alerts
|

Population-based genetic analysis in infertile men reveals novel mutations of ADAD family members in patients with impaired spermatogenesis

Abstract: The testis-specific adenosine deaminase domain-containing (ADAD) protein family, including ADAD1 and ADAD2, has been confirmed to be essential in mouse male fertility. However, the roles of ADAD1 and ADAD2 in human reproductive biology are unclear. Herein, whole exome sequencing (WES) was conducted for 337 infertile patients to detect pathogenic variants in ADAD1 and ADAD2. Importantly, a novel deleterious biallelic variant of NM_001159285.2:c.1408G > T (p.V470F) and NM_001159285.2:c.1418A > G (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Our analyses show that loss of ADAD1 leads to reduced sperm motility along with distinct sperm head morphological defects, in particular reduced DNA compaction and overall head volume. A recent study suggests a similar impact of ADAD1 mutation in humans as individuals with pathogenic ADAD1 mutations present with reduced sperm motility and sperm head shape abnormalities [71]. Although Adad1 mutant testes show minimal gene expression changes, the dramatic reduction of ribosome association in numerous spermatid transcripts demonstrates that ADAD1 influences translation of specific transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses show that loss of ADAD1 leads to reduced sperm motility along with distinct sperm head morphological defects, in particular reduced DNA compaction and overall head volume. A recent study suggests a similar impact of ADAD1 mutation in humans as individuals with pathogenic ADAD1 mutations present with reduced sperm motility and sperm head shape abnormalities [71]. Although Adad1 mutant testes show minimal gene expression changes, the dramatic reduction of ribosome association in numerous spermatid transcripts demonstrates that ADAD1 influences translation of specific transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…sqADAR/D-like does not appear to be cephalopod-specific as BLAST searches uncover similarities to the recently described ADAD-like molecules in other mollusks ( Zhang et al, 2023 ). ADADs act as RNA-binding molecules found to be essential for spermatogenesis in mammals ( Schumacher et al, 1995 ; Snyder et al, 2020 ; Dai et al, 2023 ). The function of ADAD-like molecules in mollusks is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In Adad2 Mut/Mut mice, we observed very few elongated spermatids or spermatozoa, suggesting that the frameshift or missense variants of ADAD2 , located in the adenosine deaminase domain, are associated with a good prognosis for testicular sperm extraction, and that the retrieved sperm might be recovered and used for ICSI. However, a recent report described a patient with asthenoteratozoospermia carrying a homozygous missense mutation of ADAD2 (c.1381C>T, p.R461W), located in the adenosine deaminase domain, the same domain as our MT1 (MT1: c.G829T, p.G277C) and MT2 (c.G1192A, p.D398N), who failed to cause pregnancy even after ICSI treatment ( Dai et al , 2023 ), suggesting that the poor-quality spermatozoa from the ADAD2 mutant patient were not sufficient to father a biological child. Therefore, ROSI might be an alternative therapy for patients harboring ADAD2 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that a homozygous stop-gain mutation in ADAD2 (c.1186C>T, p.Gln396Ter) and compound heterozygous mutations (Hg19: chr16:84012049–84224913del and c.82dupC, p.Gln28ProfsTer136) in ADAD2 might be associated with incomplete spermatogonial arrest ( Krausz et al , 2020 ). Patients with severe asthenoteratozoospermia carrying a homozygous frameshift mutation (c.17_18del, p.Gln6Argfs*3) or a homozygous missense mutation (c.1381C>T, p.Arg461Trp) in ADAD2 showed morphological deformities in both the sperm head and flagellum assembly ( Dai et al , 2023 ; Tian et al , 2023 ), suggesting that ADAD2 may affect human spermatogenesis. However, the reproductive phenotype of these ADAD2 mutations identified in humans differ from those in Adad2 ko mice, and the pathological effects of these ADAD2 mutations have not been verified in mouse models.…”
Section: Introductionmentioning
confidence: 99%